Father and Son Cistercians of the Twelfth Century: Blessed Amadeus of Hauterive, "The Elder", and Saint Amadeus, Bishop of Lausanne - Merton, Thomas (Cistercian studies quarterly, 2008)
The article presents an introduction to the article "Blessed Amadeus of Hauterive, The Elder: Monk of Bonnevaux," which focuses on the lives of two Cistercian saints called Amadeus. The saints were father and son, in which it is the son who had the official title of saint and enjoys the greater liturgical cult, while his father is accorded the title of Blessed on the grounds of his immemorial veneration.